10th AIAA Aviation Technology, Integration, and Operations (ATIO) Conference 2010
DOI: 10.2514/6.2010-9376
|View full text |Cite
|
Sign up to set email alerts
|

Sector Design and Boundary Change Considerations for Flexible Airspace Management

Abstract: In Next Generation Air Transportation System (NextGen) operations, we expect that the demand-capacity balance can be achieved by selectively managing the airspace capacity in conjunction with managing the traffic demand. In Flexible Airspace Management (FAM), the airspace complexity can be assessed a few hours ahead in order to identify sectors that could exceed their defined traffic threshold as well as sectors that are under-utilized. Using various airspace optimization algorithms, airspace can be reconfigur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…A previous study of airspace reconfiguration impact on air traffic controller workload indicated that a decrease in similarity between the original and reconfigured airspace was related to an increase in controller workload during the airspace reconfiguration [15,16]. The similarity between airspace configuration i and the original was calculated as a similarity distance, D i , where larger distance indicates less similarity.…”
Section: Airspace Similaritymentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study of airspace reconfiguration impact on air traffic controller workload indicated that a decrease in similarity between the original and reconfigured airspace was related to an increase in controller workload during the airspace reconfiguration [15,16]. The similarity between airspace configuration i and the original was calculated as a similarity distance, D i , where larger distance indicates less similarity.…”
Section: Airspace Similaritymentioning
confidence: 99%
“…Previous studies on airspace design indicated that increased number of flights with short dwell time in a sector was related to increased controller workload [15,16]. Let T i be the average number of flights with short dwell time in airspace configuration i, given by…”
Section: Number Of Flights With Short Dwell Timementioning
confidence: 99%
See 1 more Smart Citation
“…Main contributors to controller workload during the boundary change were initially identified. 32 Both areas, mixed operations in the same airspace and flexible airspace management are described below.…”
Section: Dynamic Airspace Configuration: Mixed Operations and Flexmentioning
confidence: 99%
“…Overall, the results and feedback from the study showed that Flexible Airspace is a promising concept worth further development and refinement. 32,43 A number of tradeoffs may be required in finding the most effective way to address the demand-capacity imbalance while keeping the human controller integrated and functioning meaningfully within the system. Based on the results from this study, further research can begin in addressing these issues.…”
Section: Dynamic Airspace Configuration (2009)mentioning
confidence: 99%